Factors Affecting Satisfaction and Loyalty in Public Transport using Partial Least Squares Structural Equation Modeling (PLS-SEM) - Mah, Yau Seng; Wan Hashim, Wan Ibrahim; Lo, May Chiun; Ha, Shiaw-Tong (Blue Eyes Intelligence Engineering & Sciences Publication, 2019)
With an increasing number of privately own vehicles in Malaysia, the popularity of public transports is increasingly challenged by ride-hailing services such as Grab, MyCar, JomRides and MULA. To develop effective strategies aimed at retaining users, it is necessary to understand the factors that affect users’ satisfaction and loyalty in public transport. In this study, we propose that satisfaction and loyalty in public transport are associated with five key factors: accessibility, reliability, perceived value, comfort, and safety and security. Data collected from a survey of 179 public transport users in Kuching city was used to test the research model. Partial least squares structural equation modeling (PLS-SEM) was used to analyse the data. The main findings were that safety and security, and reliability significantly affected the users’ satisfaction and loyalty in public transport, while no statistically significant relationship was found among accessibility, satisfaction and loyalty. These findings not only contribute to the theory development of transportation research but also help practitioners to develop novel strategies aimed at increasing public transport usage.